KEBIJAKAN PENGENDALIAN PENCEMARAN SUMBER AIR BERSIH PERUMAHAN SEDERHANA DI KOTA PEKANBARU (KASUS DI KECAMATAN TAMPAN) - Herman Nazar; Adnan Kasry; Zulfan Saam (Program Pascasarjana Universitas Riau, 2010)
Development Policy, Regulation and clean water resources controls in Pekanbaru Town can beachieved by constructing appropriate permit and regulation. However, the current permit andregulation do not include several important aspects such as domestic waste pollution limit forexcrement waste in individual housing. On the other hand, poor coordination for protection ofclean water resources is giving housing developer a chance to build a house according to theyown standard, which is far from expectations. In fact, from 80 houses, that have already builtand owned, indicate that only 26 percent of the houses have located septic tank 10 meter awayfrom the house’s clean water resources. Nevertheless, 90 percent of the houses do not havewater resistant septic tanks and about 40 percent the septic tank never been empty. The otherproblem is that clean water quantity 48,75 percent of the house has this issue, followed by waterodor problem 74,4 percent and the last problem is the total house has breach legal limit for theamount of coliform in their water has reached 50 percent. It is recommended that Pekanbarugovernment have to improve their current Clean Water Resources policy by creating newstandard operational procedures (SOP), and increase the supervision of housing development,especially in real estate industry in Pekanbaru Area as well as the function and sectionimprovement of current duties. When the policy is improved with SOP and supported by theincreasing of supervision and coordination, Clean Water Resources pollution can be controlledand minimise.